Fermented Gold Kiwifruit Protects Mice Against Non-Alcoholic Fatty Liver Disease in a High-Fat Diet Model - Jihye Choi; Hwal Choi; Yuseong Jang; Hyeon-Gi Paik; Hyuck-Se Kwon; Jungkee Kwon (Applied Sciences)
Gold kiwifruit is known for its high vitamin C content and various benefits. This study investigated the effects and molecular mechanisms of fermented gold kiwifruit (FGK) in a mouse model of high-fat diet (HFD)-induced obesity and hepatic steatosis. FGK powder was prepared using five strains of lactic acid bacteria: L. paracasei, Lc. lactis, L. acidophilus, L. casei, and L. helveticus. ICR mice were fed an HFD for 8 weeks to induce obesity and hepatic steatosis, and FGK supplementation was evaluated for its therapeutic potential. FGK administration significantly reduced serum levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), total cholesterol, triglyceride, and glucose compared to the HFD-only group. Histopathological analysis showed that FGK reduced lipid accumulation and hepatic lesions, as confirmed by hematoxylin and eosin (H&E) staining. Furthermore, administration of FGK activated the sirtuin 1(SIRT1)/adenosine monophosphate-activated protein kinase (AMPK) pathway and inhibited expression of the pro-inflammatory cytokines such as IL-1β, IL-6, and TNF-α in liver tissue. These findings suggest that FGK could reduce the severity of non-alcoholic fatty liver disease (NAFLD) by inhibiting fat synthesis, promoting fat breakdown, and suppressing inflammation in HFD-induced obese mice.